Changes in diatom, pollen, and chironomid assemblages in response to a recent volcanic event in Lake Galletué (Chilean Andes) - Urrutia, R.; Araneda, A.; Cruces, F.; Torres, L.; Chirinos, L.; Treutler, H.C.; Fagel, N.; Bertrand, S.; Alvial, I.; Barra, R.; Chapron, E. (Elsevier, 2007)
Several lakes in Chile are near important volcanic areas where eruption impacts can limit the quality of lacustrine sediments for reconstructing past environmental changes. In this study, we report changes in diatoms, pollen, and chironomids assemblages after a tephra deposition in Lake Galletué (Chilean Andes). A sediment core obtained from Lake Galletué (40 m water depth) was sliced in 1 cm intervals and subsamples were taken to analyze each proxy. 210Pb and 137Cs activities were measured to obtain the geochronology and mineralogical analyses were performed to determine the mineral composition of the tephra. Diatom species composition and productivity were modified when the lake received the tephra; Aulacoseira granulata decreased and was later replaced by Cyclotella af. glomerata. After the tephra input, Aulacoseira granulata abundance increased to pre-disturbance levels and Cyclotella af. glomerata decreased. These changes seem to suggest a momentary increase in lake nutrient levels after the tephra deposition. Chironomid assemblages also decreased in head capsules just after the tephra deposition, but the most important change was the replacement of Ablabesmyia by Parakiefferiella, probably due to the sedimentological changes produced by the input of coarse tephra grains. Furthermore, unlike other studies, chironomid assemblages in Lake Galletué did not show a decrease drastically in diversity within the tephra layer. The pollen analysis indicated that, prior to the volcanic event, the vegetal community was dominated by Nothofagus sp., Araucaria araucana, and Blechnum sp.-type. After the tephra deposition, the same taxa are dominant, indicating that the volcanic event seems not produce changes in the vegetation. Nevertheless, within the tephra layer it is possible to see an increase in Poaceae, which represent – due to the percolation process – the effect of eruption on the vegetation. According to our results, diatoms were the most sensitive proxy for describing the changes produced by tephra deposition into the aquatic ecosystem and, despite the noticeable changes in its sedimentological properties; the lake seems to have a high resilience capacity, allowing it to return to pre-tephra input conditions.
Keywords: Biological proxies; Tephra impacts; Lake sediment; Chilean Andes; https://purl.org/pe-repo/ocde/ford#1.05.02